In situ measurement of the dynamic yarn path in a turbo ring spinning process based on the superconducting magnetic bearing twisting system. Issue 7 (April 2020) - Hossain, M; Sparing, M; Espenhahn, T; Abdkader, A; Cherif, C; Hühne, R; Nielsch, K
The yarn tension and balloon form are the most important physical process parameters to characterize the dynamic yarn path in ring spinning. The present research work focuses on the in situ measurement of yarn tension in different regions of the yarn path in a developed turbo ring spinning tester with a friction-free superconducting magnetic bearing (SMB) twisting system and at an angular spindle speed of up to 50, 000 rpm. The influence of different parameters, such as angular spindle speeds (15, 000–50, 000 rpm), yarn counts (15–40 tex) and balloon control ring (one or multiple), were evaluated to identify the influence of acting forces, for example, centrifugal forces. The effects of these process parameters were analyzed statistically using an analysis of variance. The yarn tension between the delivery rollers and the yarn guide was measured using a modified one-roller tensile yarn tension sensor. The yarn tension between the yarn guide and the SMB system was determined with an already existing optical approach at a higher angular spindle speed. As the highest yarn tension theoretically occurs between the SMB system and the cop, it was estimated in this region by measuring the coefficient of friction between the yarn and the yarn guide using the friction module of the constant tension tester equipment. The maximum balloon diameter was determined from the recorded balloon form between the yarn guide and the SMB system with respect to different angular spindle speeds. The results provide valuable information about the highest possible spinnable speed and enable a better understanding of the dynamic yarn path in the SMB spinning system.